1990
DOI: 10.1007/bf00144600
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pore-structure on hysteresis in relative permeability and capillary pressure: Pore-level modeling

Abstract: The effect of pore-structure upon two-phase relative permeability and capillary pressure of strongly-wetting systems at low capillary number is simulated. A pore-level model consisting of a network of pore-bodies interconnected by pore-throats is used to calculate scanning loops of hysteresis between primary drainage, imbibition and secondary drainage. The pore-body to pore-throat aspect ratio strongly influences the pattern of hysteresis. Changes in the patterns of hysteresis often attributed to consolidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
203
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(229 citation statements)
references
References 83 publications
(76 reference statements)
12
203
0
2
Order By: Relevance
“…As has been noted by many authors [Chatzis and Dullien, 1977;Wilkinson and Willemsen, 1983] the coordination number will influence the network model behavior significantly, both in terms of breakthrough and relative permeability. In order to match the coordination number of a given rock sample, which typically is between 3 and 8 [Jerauld and Salter, 1990], it is possible to remove throats at random from a regular lattice [Dixit et al, 1997[Dixit et al, , 1999, hence reducing the connectivity. The pore and throat size distributions will also affect the estimated macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
“…As has been noted by many authors [Chatzis and Dullien, 1977;Wilkinson and Willemsen, 1983] the coordination number will influence the network model behavior significantly, both in terms of breakthrough and relative permeability. In order to match the coordination number of a given rock sample, which typically is between 3 and 8 [Jerauld and Salter, 1990], it is possible to remove throats at random from a regular lattice [Dixit et al, 1997[Dixit et al, , 1999, hence reducing the connectivity. The pore and throat size distributions will also affect the estimated macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, both computer-generated networks and real-shale networks using FIB/SEM will be used. For computer-generated networks, it is usually assumed that pore and throat sizes are spatially uncorrelated in the regular-topological networks, but previous studies have found that the size relationship between the adjacent pores and throats has certain effects on the permeability of the networks [24]. In order to guarantee the spatial correlation between pores and throats, a PNM based on the work of Blunt et al [25] in which large pores prefer to be connected with large throats is employed in this study.…”
Section: Gas Flow Model For Nanoporous Kerogenmentioning
confidence: 99%
“…After this legendary work, pore-network models, mainly dominated by quasi-static pore-network models, were developed and applied to reservoir engineering and hydrogeology problems. The pore-network modelling opened up a new horizon in understanding the constitutive relations for two-phase flow such as capillary pressure and relative permeability curves [10,11], and at a later stage exploring the transport phenomena in porous media [12]. With further technological developments in micromodel and X-ray imaging facilities and computational infrastructures, quantitative pore-network models were further developed [13].…”
Section: Introductionmentioning
confidence: 99%